(untitled) (Annual of the Faculty of Philosophy in Skopje, 2016)
This research used a convenience sample. It was included 62 respondents of which 31 reported domestic violence in the centers for social work in the period from October 2015 to March 2016. The remaining 31 women reported that they want to participate in research and served as a control group that was likened to a group of women who reported domestic violence. Results obtained by testing specific hypotheses have shown that domestic violence does not affect rising risk of suicidal behavior, partly confirmed the main hypothesis which asserts that domestic violence affects the occurrence of PTSD, increased anxiety, depression and risk of suicide behavior.